Pengaruh Brand Image, Korean Wave Dan Brand Ambassador, Terhadap Keputusan Pembelian Produk Di E-Commerce Tokopedia (Studi Kasus Generasi Z Di Dki Jakarta) - Silalahi, Marylin Xaverina (2022)
This study is quantitative research that aims to determine the influence of brand image, Korean wave, and brand ambassadors in making purchasing decisions. This study uses Generation Z which collects 100 respondents who use Tokopedia and are active in the D.K.I. Jakarta. The technique that the author uses in collecting data is using non-probability sampling and using a purposive sampling method. The data was collected using a questionnaire in the form of a google form which was then distributed through social media, namely Instagram, Twitter, Line, and WhatsApp. This research uses PLS (Partial Least Square) analysis technique assisted by SmartPLS 0.3 software. The results obtained in this study are: (1) Brand Image variable is positive and has a significant effect on purchasing decisions (2) Korean Wave variable is positive and has a significant effect on purchasing decisions (3) Brand Ambassador variable is positive and has a significant effect on purchasing decisions. From the results obtained, Tokopedia is expected to continue to innovate both with the help of the Korean wave phenomenon in maintaining their brand image with the help of brand ambassadors who reach out to attract consumer purchasing decisions at Tokopedia.